Lipid and protein stability of partially defatted walnut flour (Juglans regia L.) during storage - Labuckas, Diana (2011)
Partially defatted walnut flour (WF) was stored (25 °C, 800 Lux) for an 8-month period and evaluated monthly in some protein properties and oil oxidative parameters. Transparent plastic-laminated (WFPL) and plastic-laminated, aluminium-coated (WFAC) packages were used. During the first 3 months, samples were more susceptible to endogenous hydrolysis; an increase in soluble peptide concentration was determined for both WFAC and WFPL. Minor changes between WFAC and WFPL were observed in protein electrophoretic patterns along storage period, but no differences were determined in total protein solubility. However, a progressive reduction in water-holding capacity (47% from time 0 to month 8) was observed for WFPL. A major effect of packaging material was found on lipid-quality parameters. Packaging materials’ barrier to light effectively protect WF against polyunsaturated FA degradation and oil oxidation. Lipids from WF stored in plastic-laminated packages showed decreasing double-bond index values (from 1.71 at initial time, to 1.45 after 6 months of storage) and increasing oxidation rates along storage test. Aluminium-coated packages can be used to keep quality of WF for 8 months at room temperature.